THE EFFECT OF E-WOM AND TOURISM PRODUCT ATTRIBUTES ON VISITING DECISIONS IN LAKE CIPONDOH TOURIST DESTINATION, TANGERANG CITY, BANTEN PROVINCE - Heny Ratnaningtyas; Rahmat Ingkadijaya; Linda Desafitri (Universitas Islam Lamongan, 2022)
This study aims to determine the effect of E-WOM and tourism product attributes on visiting decisions. The population in this study were visitors who traveled to Lake Cipondoh, Tangerang City. The sample in this study amounted to 100 respondents. The sampling technique used was accidental sampling. The partial research results of E-WOM and tourism product attributes had a significant effect on visiting decisions. Lake Cipondoh managers are expected to increase visitor enthusiasm by creating websites and social media, then adding attractions and special attractions.